Impact of tree isolation on aboreal and ground ant communities in cleared pasture in the Atlantic rain forest region of Bahia, Brazil - Majer, Jonathan; Delabie, J. (1999)
The Atlantic rain forest of south-eastern Brazil has been substantially cleared, resulting in the creation of a fragmented landscape. In addition to the small fragments of forest that remain, the pasture is often scattered with isolated trees. This paper investigates the capacity of these isolated trees to support representatives of the original Atlantic rain forest ant communities and also how these arboreal ants interact with the disturbance-associated ant fauna of the pasture beneath them. Twenty trees in the grassland, representing a range of distances from the forest, and 10 trees within the forest, were selected for sampling. Arboreal ants were sampled by hand collection and chemical knockdown, while the ants on the ground beneath were sampled by pitfall traps and Winkler sacks. Pasture trees supported a moderately high richness of arboreal ant species. The richness of ants on pasture trees appears to be independent of distance from forest, although this might become a significant factor on trees that are more isolated than those studied here. Ant species richness on pasture trees is higher if the trees are large, support a high epiphyte load and are native to the area. Isolated trees within the agricultural matrix therefore play some role in conserving elements of the original forest ant fauna. Since some of the species on pasture trees have been observed to reach dominant or sub-dominant status in nearby forest and cocoa farms, they may play some role in limiting pest outbreaks in the pasture close to the trees. If this is so, there may be a case for retaining an adequate density of trees to enable the influence of arboreal ants to extend over as much pasture as possible.